Cultural construction of religious tolerance in urban socio-cultural change: Evidence from Salatiga, Indonesia - Sukardi Sukardi; Muhammad Wildan; Badrun Badrun (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines how religious tolerance is culturally constructed amid ongoing socio-cultural changes in Salatiga, Indonesia. Existing academic studies on pluralism in Indonesia generally emphasize theological discourse and institutional dialogue, resulting in limited empirical attention to the everyday cultural processes that support interreligious harmony. Using a qualitative interpretive design, data from in-depth interviews, participatory observation, and document analysis involving seven interreligious informants were analyzed through interpretive thematic analysis. Findings indicate that tolerance is produced through routine social interactions, shared communal practices, and Islamic ethical values embedded in culture, while globalization, urbanization, and the circulation of digital religion generate new symbolic tensions that require ongoing negotiation. This study demonstrates that religious tolerance operates as an adaptive cultural process that connects ethical religion, lived social practices, and socio-cultural transformation, offering a contextual theoretical model of culturally rooted plural coexistence in late modern urban societies.